Manifest Need Satisfaction in male and Female Counsellors - Harvey, Brian; France, Honoré (Canadian Journal of Counselling and Psychotherapy, 2012)
The present study examines the manifest needs of achievement, dominance ,autonomy, and affiliation of counsellors. Results indicate that there are similarities in male and female counsellors regarding achievement, dominance, and autonom yand that there is a consistent trend for male counsellors to have higher needs for affiliation than do female counsellors on the job. Years of teaching and counselling experience appear not to influence manifest needs on the job. Affiliation needs, however, show a marginally significant increase with years of teaching experience. Experience related to counselling also affects the need for affiliation, affiliation needs increasing as related experience increases. The data are discussed in termsof developing counsellor training programs, of employing strategies for enhancin gthe counsellor's well-being on the job, and, hence, of improving the delivery of counselling services.